ENGAGEMENT E QUALIDADE DO SONO E MAIS CONEXÕES DO BURNOUT ACADÊMICO. - Andre Luiz Sbroggio Junior; Hugo Machado Sanchez; Whaine Morais Arantes Filho; Eliane Gouveia de Morais Sanchez; Barabara Morais Arantes; Willian Deivis Guarienti; Jefferson José De Souza Neto; Tallys Cezary Gomes Amaral (UniEVANGÉLICA, 2018)
Objective: to analyze the prevalence of engagement that correlates with positive symptoms of burnout syndrome and correlate with sleep quality and sociodemographic variables. Methods: This is a cross-sectional study conducted at the University of Rio Verde using an instrument constructed by the author himself and the second instrument UWES-S - Utrecht Work Engagement Scale-Student that measures and correlates with data from the sociodemographic instrument itself with the PSQI-Pittsburgh Quality Sleep index instrument that allows evidence of changes in sleep. Results: 228 questionnaires of undergraduate students grouped in 4 major areas (Humanities, Health, Exact and Agrarian) were verified, with a mean of 3.51 ± 6.2 in the health group, as measured by the T-test under the "vigor" sphere of the UWES-S, there was a statistical difference between the male sex (ρ = 0.03), in the comparison by areas with the UWES-S sphere there were differences in the "Dedication" spheres when compared (p = 0.00) and Health x Human, in the sphere of "Absorption", statistical difference was observed when compared to Health x Agrarian (p = 0.00) and Health x Exact (p = 0, 04). There was no statistical difference when comparing the PSQI with the other data. Conclusions: Engagement as a construct is recent in Brazil. His knowledge provided a fresh look at the academic context, but there is a need for additional research to investigate how the different factors affecting student attrition and involvement in the study.